The Constraints and Prospects of Integrating ICT in Bangladesh's Madrasa Education: Data and Explanations from Dhakil-level - Shumshunnahar, Shumshunnahar; Ruma, Arifa Rahman; Amin, Ruhul (Pancasila International Journal of Applied Social Science, 2025)
This research examines the challenges and opportunities of incorporating Information and Communication Technology (ICT) into Dhakil-level Madrasa teaching in Bangladesh. Despite the government's attempts to modernize education, ICT adoption in Madrasas remains much lower than in mainstream schools, with just 25% incorporating ICT into their curricula, compared to more than 70% in secondary schools. The study takes a mixed-methods approach, combining quantitative surveys and qualitative interviews to evaluate the present level of ICT infrastructure, teacher readiness, and cultural attitudes toward ICT integration in Madrasas. The findings show that poor infrastructure, particularly in rural regions, and a lack of educated instructors are essential hurdles to effective ICT adoption. Cultural and ideological resistance within the Madrasa community hinders efforts to integrate new technology, with some stakeholders concerned that ICT may undermine traditional Islamic instruction. However, the report also highlights significant opportunities for ICT integration, such as government measures to improve teacher training and revise curriculum to incorporate ICT components. The study indicates that, while there are significant problems, ICT can potentially improve religious and secular education. To ensure effective ICT integration, focused expenditures in infrastructure, teacher training, and culturally relevant curriculum creation are required. These efforts can help bridge the digital gap and provide Madrasa students with the skills they need to succeed in today's technology-driven environment.